Common Glossary - E-REI (E- Revista de Estudos Interculturais, 2025)
Common Glossary The glossary covers a wide range of concepts: Climate Change; Co-creation; Community Mapping; Cosmology; Creativity; Cultural Ecosystem Services; Cultural Policy; Cultural Studies; Culture; Decolonial Epistemologies; Decolonization; Education; Environmental Justice; Glocal; Heritage; Heritage Commodification; Hybrid; Intercultural; Interdisciplinary; Intergenerational; Intersections; Interspecies; Interspecies Assemblies; Local Communities; More-than-humans / Other-than-human lifeforms; Native; Policy Effectiveness; Polycrisis; Power (in Cultural Studies); Radical; Sea Forum; Stuart Hall; Sustainability; Transdisciplinarity; Transdisciplinary Learning; Transformative Change.